Exogenous thyroxine improves glucose intolerance in insulin-resistant rats. Issue 3 (March 2017) - Vazquez-Anaya, Guillermo; Martinez, Bridget; Soñanez-Organis, José G; Nakano, Daisuke; Nishiyama, Akira; Ortiz, Rudy M
Abstract : Both hypothyroidism and hyperthyroidism are associated with glucose intolerance, calling into question the contribution of thyroid hormones (TH) on glucose regulation. TH analogues and derivatives may be effective treatment options for glucose intolerance and insulin resistance (IR), but their potential glucoregulatory effects during conditions of impaired metabolism are not well described. To assess the effects of thyroxine (T4 ) on glucose intolerance in a model of insulin resistance, an oral glucose tolerance test (oGTT) was performed on three groups of rats ( n  = 8): (1) lean, Long Evans Tokushima Otsuka (LETO), (2) obese, Otsuka Long Evans Tokushima Fatty (OLETF) and (3) OLETF + T4 (8.0 µg/100 g BM/day × 5 weeks). T4 attenuated glucose intolerance by 15% and decreased IR index (IRI) by 34% in T4 -treated OLETF compared to untreated OLETF despite a 31% decrease in muscle Glut4 mRNA expression. T4 increased the mRNA expressions of muscle monocarboxylate transporter 10 ( Mct10 ), deiodinase type 2 ( Di2 ), sirtuin 1 ( Sirt1 ) and uncoupling protein 2 ( Ucp2 ) by 1.8-, 2.2-, 2.7- and 1.4-fold, respectively, compared to OLETF. Activation of AMP-activated protein kinase (AMPK) and insulin receptor were not significantly altered suggesting that the improvements in glucose intolerance and IR were independent of enhanced insulin-mediated signaling. The results suggest that T4 treatment increased the influx of T4 in skeletal muscle and, with an increase of DI2, increased the availability of the biologically active T3 to upregulate key factors such SIRT1 and UCP2 involved in cellular metabolism and glucose homeostasis.